Analisis Framing Berita Kasus Polisi Smackdown Mahasiswa Di Tangerang Di Media Online Detik.Com - Selvia Melika; Aliasan; Ahmad Harun Yahya (CV. ITTC INDONESIA, 2024)
Framing Analysis of Student Police Smackdown Case News in Tangerang on Detik.com Online Media is the title of this research paper. An Indonesian news site called Media Detik.com. The way Media Detik.com produces and presents news about the stabbing of Tangerang Police students is an articulation of the problems in this thesis. The